The Role of Cognitive Potential in Predicting First-Semester GPA of KIP-Kuliah Scholarship Recipients - Prinska Damara Sastri; Recky Recky; Rifqi Farisan Akbar (International Journal of Marketing & Human Resource Research, 2026)
This study aims to investigate the influence of cognitive potential, measured via the Wonderlic Personnel Test (WPT), on the first-semester Grade Point Average (GPA) of KIP-Kuliah scholarship recipients (Class of 2025) at Universitas Indonesia Membangun (INABA). Using a saturated sampling technique, 94 participants were involved, predominantly female, aged 19, from the Communication Science program, with average IQ scores categorized as "Low Average" (80-90). Data were analyzed using simple linear regression, supported by classical assumption tests including normality, multicollinearity, and autocorrelation. The findings reveal a significant influence of cognitive potential on GPA (p < .05). Notably, the coefficient of determination (R² = .983) indicated that cognitive potential accounts for 98.3% of the variance in academic performance, with only 1.7% attributable to external factors. However, the regression coefficient (B = -2.185) indicated a significant negative direction, suggesting that higher cognitive scores within this specific group did not correspond to higher academic achievement during the first-semester transition. This phenomenon highlights a critical gap in academic adaptation, wherein students with "Low Average" cognitive profiles may struggle with the heightened analytical demands of higher education in the absence of adequate self-regulated learning strategies. These results underscore the need for institutional interventions, such as specialized academic mentoring, to support scholarship recipients in maintaining their academic eligibility.